Edukasi Pencegahan Cyberbullying di Media Sosial melalui Pemanfaatan Teknologi Digital untuk Siswa SMPN 1 Sembalun - Sandi, Arnila Sandi; Yahya; Hizbul Izzi; Abdul Aziz (Universitas Hamzanwadi, 2025)
The rapid development of digital information and communication technology has brought positive and negative impacts, as well as new challenges for adolescents, especially in the use of social media. One problem that often arises is cyberbullying, which can negatively impact students' mental and social health. Cyberbullying is bullying carried out through social media or digital media, which can disrupt the victim's mental health. To reduce this incident, we conducted cyberbullying prevention education at the junior high school level. This activity aims to provide education on cyberbullying prevention through the use of digital technology to students of SMPN 1 Sembalun. The implementation method included interactive socialization and discussions on the safe and responsible use of social media. The results of the activity showed an increase in students' knowledge and awareness of the dangers and ways to prevent cyberbullying on social media. In addition, students were able to practice digital ethics in their daily online interactions. This activity is expected to be the first step in establishing a positive digital literacy culture in the school environment and can prove that digital technology-based education is effective in improving digital literacy and shaping students' positive character in the digital era.